Contribution to the knowledge of the butterfly diversity (Hesperoidea & Papilionoidea) of Banja Luka, Bosnia and Herzegovina - Branislava Dukić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The paper deals with the fauna of butterflies in the Banja Luka area, located in the northwest part of the Republic of Srpska (Bosnia and Herzegovina). The paper presents data from the field research and literature. The total number of registered species for the area of Banja Luka is 93, which is quite well considering the size of the researched area. However, the number of species registered in the last survey is about 16% less than the total registered number for this area, which could indicate certain negative trends.